2003
DOI: 10.1023/b:ejep.0000036571.00320.b8
|View full text |Cite
|
Sign up to set email alerts
|

Why do Some Countries Publish More Than Others? An International Comparison of Research Funding, English Proficiency and Publication Output in Highly Ranked General Medical Journals

Abstract: National factor(s) influencing publication output in the highest ranked medical journals are largely unknown. We sought to examine the relationship between national research funding and English proficiency on publication output. We identified all original research articles appearing in the five highest ranked general medical journals between 1997 and 2001. Using the country of the corresponding author as the source nation for each article, we determined a standardized publication rate across developed nations.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
188
0
18

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(213 citation statements)
references
References 19 publications
7
188
0
18
Order By: Relevance
“…For example, Brazilian researchers with good English writing abilities outperform those with poor ones in terms of published papers, number of citations, and h-indices (Vasconcelos et al 2008). On a global comparison, English proficiency is a good predictor of publication output in top medical journals, even more than total research spending (Man et al 2004). Thus, at all levels, from individuals to countries, NES countries have an advantage over non-NES, especially over those with poor English training.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Brazilian researchers with good English writing abilities outperform those with poor ones in terms of published papers, number of citations, and h-indices (Vasconcelos et al 2008). On a global comparison, English proficiency is a good predictor of publication output in top medical journals, even more than total research spending (Man et al 2004). Thus, at all levels, from individuals to countries, NES countries have an advantage over non-NES, especially over those with poor English training.…”
Section: Introductionmentioning
confidence: 99%
“…Obstacles to publication may be numerous. English language proficiency [16,34] or the discretion of journals to publish material deemed to be important and appeal to the primary reader base [27] might have a large impact on successful publication. The need for orthopaedic research from the developing world cannot be understated given the well-documented increasing burden of disease.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of English not only limits the spread of science to non-English countries, but also prohibits these countries' communication with the rest of the world. For example, Man et al (2004) found that there is a significant relationship between national spending on research and TOEFL (Test of English as a Foreign Language, a measure of English proficiency) scores with the publication output of developed countries in highly ranked general medical journals.…”
Section: Discussionmentioning
confidence: 99%